Financial Literacy and Social Media on Student Investment Decisions - Alecia, Brigitta; MN, Nuryasman (Universitas Bunda Mulia, 2025)
This study aims to evaluate the influence of financial literacy and social media usage on students' investment decisions in the DKI Jakarta area. In today's digital era, students, as part of the younger generation, have broad access to financial information and investment platforms. However, they often face challenges in making sound investment decisions. This research adopts a quantitative approach, collecting data through questionnaires/distributed to 283 active student investors. Data analysis was conducted using the/Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The findings reveal that financial literacy has a significantly positive impact on investment decision-making. A solid understanding of basic financial concepts, risk management, and portfolio diversification helps students make more targeted investment decisions. Furthermore, social media also plays a significant role by providing real-time information and shaping students' perceptions of investment opportunities. This encourages them to invest more intelligently and responsibly. This study is expected to contribute to educational institutions in designing more effective financial education programs while also serving as a guide for financial industry players to leverage social media wisely in supporting financial literacy and inclusion. Thus, the findings of this research can serve as a reference for developing strategies that better support students' investment decision-making and foster an inclusive and sustainable investment ecosystem.